EAT-Brazil award for tobacco control: a brief description of its first edition - Rodrigues Pinto Corre︢a, Paulo César; Brinker, Titus Josef (Revista da Associação Médica Brasileira, 2019)
Smoking is a major global risk factor for preventable death and disability. EAT is an acronym for Education Against Tobacco, a multinational network of physicians and medical students that aims to improve tobacco control by means of school-based prevention targeted at adolescents through counseling, use of software and support materials. The first EAT-Brazil Award, launched in March 2018, was a competition designed to encourage the proposal of objective solutions for tobacco control in Brasil, and identify new talents in the area. Brazilian undergraduate students from any field of study could submit a one-page essay on the subject, competing for the amount of R$ 1000.00 (one thousand reais). There were a total of 39 applicants (20 women and 19 men) from 9 Brazilian states and 18 undergraduate programs, with a mean age of 22.5 years (SD = 3.7). Data from an online anonymous questionnaire answered after the submission of their essays revealed that most applicants were students of institutions from in the state of Minas Gerais (n = 26/39; 66.6%), studied medicine (n = 20/39, 51.3%), and had no prior knowledge of the EAT-Brazil Network (n = 27/39, 69.2%). The winner of the award was Lucas Guimarães de Azevedo, a fourth-year medical student at Federal University of Western Bahia.The next editions of the award should focus on increasing the number of applicants and diversifying their geographical distribution.